Análisis de la gestión recaudadora de la cartera de impuestos administrados por el Gobierno Autónomo Descentralizado Municipal del cantón Chone - Freire Loor, Bryan Stalin (2023)
In Ecuador, Autonomous Decentralized Governments (GAD) face significant challenges in managing overdue tax and fee portfolios, which in turn impact the execution of public infrastructure projects. This study focused on analyzing the tax collection management of the Autonomous Decentralized Municipal Government (GADM) in Chone Canton during the period 2018-2022, with the aim of proposing improvements in collection practices. Research techniques such as interviews, observation, and document analysis were employed. Various categories of outstanding accounts were identified, including taxes, fees, contributions, investment income, and fines. The collection strategy was based on strict adherence to tax regulations, supported by mass communication directed at taxpayers and public infrastructure projects highlighting the benefits of fiscal contributions. A significant achievement was the recovery of 40% of the outstanding public debt between July 2021 and December 2022. A Improvement Plan was designed to increase revenue from less-attended categories as part of an effort to promote local business development and tourism. This approach seeks to strengthen fiscal management and stimulate socio-economic progress in the selected municipality, contributing to the overall learning process.